Application Of Marriage Age According To Law Number 16 Of 2019 Concerning Amendments To Law Number 1 Of 1974 Concerning Marriage (Study At The Malang Regency Religious Court) - Usman Thalib, Jihad (International Significance of Notary, 2024)
Abstract : This study is behind the determination of the age limit for marriage is very important because in addition to wanting biological maturity also psychological maturity. So in the general explanation of the marriage law, it is stated that the bride and groom must mature their body and soul to be able to carry out the marriage so that the marriage runs well without ending in divorce and gets good and healthy offspring. Researchers formulate the problem of how to apply the age of marriage according to Law Number 16 of 2019 concerning marriage in Malang Regency, what factors make the people of Malang Regency marry below the age of marriage, and how the efforts and constraints of the Religious Court overcome the problem of the provision of the age limit for marriage in Malang Regency. This research uses normative and empirical research in the form of a statutory approach, a conceptual approach, and a sociological approach. Research data sourced from primary obtained from field studies and secondary data sourced from primary, secondary, and tertiary legal materials which are then analyzed based on descriptive qualitative analysis. The results and first discussion show that the implementation of the age limit for marriage in Malang Regency can be said to be ineffective when compared to before the amendment of Law Number 19 of 2019. Second, factors that cause underage marriage include economic factors, educational factors, and cultural factors, so it does not rule out the possibility of underage marriage does not bring happiness as the purpose of marriage itself. Third, the efforts of the Malang Regency Religious Court include direct socialization and legal counseling to the community, especially regarding changes in the age limit for marriage which refers to Law Number 16 of 2019 that children who can carry out marriage are at least 19 years old.Keywords : Change, Age Limit, Marriage